Digitalization of public governance in the EAEU countries - V. A. Sapryka; A. V. Pastyuk; N. I. Kulakova (Цифровая социология)
Various aspects of digitalization of public administration in the countries of the Eurasian Economic Union are considered. It is noted that digitalization is spontaneous and comprehensive, and also affects almost all spheres of public relations, including the system of public administration. In this regard, there is a need to develop a joint interstate policy in the field of institutionalization of the processes of digitalization of society. Digitalization is defined as a set of digital transformation of the processes of economic entities and the creation of digital products and services, and not just as digitization - the transfer of data from analog form to digital. In turn, the definition of the term “public administration” can be formulated as a set of mechanisms, processes, relationships and institutions through which citizens of the state, their associations express their interests, exercise their rights and obligations and settle differences. The analysis of the practice of institutionalization of the processes of digitalization of public administration demonstrates the fact that the main regulatory norms and practices in this sphere are fixed within the framework of national target programs.This article analyses the program and target documents of all the member countries of the Eurasian Economic Union, affecting the digitalization regulation processes, the need to institutionalize the processes of digitalization of government and society, as well as the introduction of modern technologies in the practice of public administration. At the same time, the common element of all strategies, concepts and programs is only the digitalization of the process of providing public services, and the other parameters of the target documents are largely different. In this regard, it is required to form a unified model of digitalization of public administration of the Eurasian Economic Union on the basis of a unified strategy.